Constraining the Metallicities, Ages, Star Formation Histories, and Ionizing Continua of Extragalactic Massive Star Populations - Chisholm, J.; Rigby, J. R.; Bayliss, M.; Berg, D. A.; Dahle, H.; Gladders, M.; Sharon, K. (The Astrophysical journal, 2019)
We infer the properties of massive star populations using the far-ultraviolet stellar continua of 61 star-forming galaxies: 42 at low redshift observed with the Hubble Space Telescope and 19 at z ~ 2 from the MegaSaura sample. We fit each stellar continuum with a linear combination of up to 50 single-age and single-metallicity starburst99 models. From these fits, we derive light-weighted ages and metallicities, which agree with stellar wind and photospheric spectral features, and infer the spectral shapes and strengths of the ionizing continua. Inferred light-weighted stellar metallicities span 0.05–1.5 Z(sub ⊙) and are similar to the measured nebular metallicities. We quantify the ionizing continua using the ratio of the ionizing flux at 900 Å to the non-ionizing flux at 1500 Å and demonstrate the evolution of this ratio with stellar age and metallicity using theoretical single-burst models. These single-burst models only match the inferred ionizing continua of half of the sample, while the other half are described by a mixture of stellar ages. Mixed-age populations produce stronger and harder ionizing spectra than continuous star formation histories, but, contrary to previous studies that assume constant star formation, have similar stellar and nebular metallicities. Stellar population age and metallicity affect the far-UV continua in different and distinguishable ways; assuming a constant star formation history diminishes the diagnostic power. Finally, we provide simple prescriptions to determine the ionizing photon production efficiency (ξ(sub ion)) from the stellar population properties. The ξ(sub ion) inferred from the observed star-forming galaxies has a range of log(ξ(sub ion)) = 24.4–25.7 Hz erg(exp −1) that depends on the stellar population age, metallicity, star formation history, and contributions from binary star evolution. These stellar population properties must be observationally determined to accurately determine the number of ionizing photons generated by massive stars.